Gambaran kinerja kepala ruangan dan ketua tim di Ruang Model Praktik Keperawatan Profesional (MPKP) Rumah Sakit Jiwa Daerah Provinsi Jambi - Nini Afriani; Nofrida Saswati; Rian Maylina Sari (MAHESA : Malahayati Health Student Journal, 2021)
ABSTRACT: DESCRIPTION OF THE PERFORMANCE OF THE HEAD OF THE ROOM AND TEAM HEAD IN THE MODEL ROOM OF PROFESSIONAL NURSING PRACTICE (MPKP) A REGIONAL MENTAL HOSPITAL OF JAMBI PROVINCE Background  The Model of Professional Nursing Practice (MPKP) has been implemented in several countries, including in various Indonesian asylums. Jambi Provincial Mental Hospital has implemented a Model of Professional Nursing Practice (MPKP), but its implementation has not been implemented in its entirety. The role and function of the head of the room and the head of the team is critical to the development of the performance of the implementing nurses in the space that has implemented the MPKP. This research aims to find out the picture of the performance of the head of the room and the team leader in the Model Room of Professional Nursing Practice (MPKP) of Jambi Provincial Psychiatric Hospital year 2020.Method This research is quantitative research. This research was conducted in the MPKP room of Jambi Provincial Psychiatric Hospital conducted on March 26 – April 6, 2020. The population in this study was the entire head of the room as many as 10 people and the team leader as many as 20 people in the MPKP room at Jambi provincial asylum in March-April 2020. The sample in this study was as many as 30 people with total sampling techniques. Data collection is done by interviewing and filling out questionnaires. Data analyzed univariately.Result: The results of this study showed that the head of the room had a good performance and was less good each as much as 5 (50%) Respondents. The team leader had a good performance and was underperforming by 10 (50%) of each respondent.Conclusion The results of this study show that both the head of the room and the team leader has not been optimal performance. It is recommended that the hospital conduct training and training in the form of workshops and seminars to increase the knowledge of the head of the room and the head of the team to implement 4 pillars of MPKP. Keywords: Performance, Katim, Karu, MPKP INTISARI : GAMBARAN KINERJA KEPALA RUANGAN DAN KETUA TIM DI RUANG MODEL PRAKTIK KEPERAWATAN PROFESIONAL (MPKP) RUMAH SAKIT JIWA  DAERAH PROVINSI JAMBI Latar Belakang Model Praktek Keperawatan Profesional (MPKP) telah dilaksanakan dibeberapa negara, termasuk di berbagai rumah sakit jiwa Indonesia. Rumah Sakit Jiwa Daerah Provinsi Jambi telah menerapkan Model Praktek Keperawatan Profesional (MPKP), namun pelaksanaannya belum secara keseluruhan. Peran dan fungsi kepala ruangan dan ketua tim sangat penting untuk perkembangan kinerja perawat pelaksana pada ruang yang telah menerapkan MPKP. Penelitian ini bertujuan untuk mengetahui gambaran kinerja kepala ruangan dan ketua tim di Ruang Model Praktik Keperawatan Profesional (MPKP) Rumah Sakit Jiwa Daerah Provinsi Jambi Tahun 2020.Metode Penelitian ini adalah penelitian kuantitatif. Penelitian ini dilakukan di ruang MPKP Rumah Sakit Jiwa Daerah Provinsi Jambi yang dilakukan pada tanggal 26 Maret – 6 April 2020. Populasi dalam penelitian ini adalah seluruh kepala ruangan sebanyak 10 orang dan dan ketua tim sebanyak 20 orang di ruang MPKP di Rumah Sakit Jiwa Daerah Provinsi Jambi pada bulan Maret-April 2020. Sampel dalam penelitian ini sebanyak 30 orang dengan teknik total sampling. Pengumpulan data dilakukan dengan wawancara dan pengisian kuesioner. Data dianalisis secara univariat.Hasil Hasil penelitian ini menunjukkan bahwa kepala ruangan memiliki kinerja yang baik dan kurang baik masing-masing sebanyak 5 (50%) responden.Ketua tim memiliki kinerja yang baik dan kurang baik masing-masing sebanyak 10 (50%) responden.Kesimpulan Hasil penelitian ini menunjukkan bahwa baik kepala ruangan dan ketua tim memiliki kinerja yang belum optimal. Sebaiknya rumah sakit mengadakan pelatihan dan diklat dalam bentuk workshop dan seminar agar menambah pengetahuan kepala ruangan dan ketua tim untuk menerapkan 4 pilar MPKP. Kata Kunci: Kinerja, Katim, Karu, MPKP